Development of RME-based Teaching Modules to Improve Problem-Solving Skills and Mastery of IPAS Concepts for Junior High School Students - Lisdiani Pamio; Armiati; I Made Arnawa; Yulyanti Harisman (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop a teaching module based on RME that is valid, practical, and effective for class VII SMP, with a focus on improving the ability to solve problems with mathematical students. We developed the modules by considering the local context and culture, adhering to RME measures, and emphasizing the use of relevant and conceivable situations for students. We utilized the Plomp development model, which encompasses the stages of investigation, creation, and evaluation. We tested the prototype and assessment of this teaching module on participants enrolled in class VII at SMP N 1 Ranah Batahan. The research results demonstrate that the developed teaching modules have high validity (89.33%), practicality (89.60%), and proven effectiveness, as evidenced by an average score of 85.50% among the test study students.  In addition to enhancing the mathematical skills of students, the RME approach also enhances the study of IPAS (Natural and Social Sciences). The development of problem-solving and critical thinking skills through this module enhances students' understanding of natural and social phenomena. Therefore, this teaching module not only promotes mathematical achievement but also fosters integrative and holistic learning within the framework of IPAS.